The Sex Pheromone Content of The Spodoptera Exigua (Hubner) Under Artificial and Natural Diets - Kadis Mujiono; Witjaksono Witjaksono; Nugroho Susetya Putra (Chemical Engineering Diponegoro University, 2015)
The control of the Spodoptera exigua Hubner (Lepidoptera: noctuidae) through sex pheromones is feasible by mass trapping, mating disruption, and population monitoring. Both synthetic sex pheromones and virgin females were used on the mass trapping and population monitoring methods as attractant source. The virgin females must be available through the mass rearing without affected on its pheromone content production. Therefore, a study on the response of the female’s pheromone which reared by artificial and natural diets was important to be done. The GCMS analysis result had shown that female’s pheromone glands extract which had reareded by natural diets contained tetradecan-1-ol (0.23%) pheromone compounds and several other compounds, such as hexadecane (14.31%), heptadecane (0.42%), nonadecane (1.09%), and beta-caryophyllene (1.37%). Meanwhile, only tridecanol (3.39%), hexadecane (8.52%), nonadecane (0,23%), and trans-caryophyllene (3.11%) compounds had been found on the artificial ones. The cross-copulation test showed that both types of moths could do mating. The field trapping test showed that both extracts were attractive to males